INTEGRASI KEILMUAN PESANTREN: Studi Korelasi Antara Ilmu Agama dan Ilmu Umum di Pondok Pesantren Nurul Huda Yaspin - Moch Fahmi Amiruddin; Dian (STAI Pelabuhan Ratu, 2021)
This study aims to find out how the concept of integrating religious knowledge with general science is at the Nurul Huda Yaspin Islamic Boarding School and how to apply the integration of religious knowledge and general science at the Nurul Huda Yaspin Islamic Boarding School. This type of research is case study research or field research, where researchers go directly to the field to obtain data and information on the research carried out. Meanwhile, this research approach uses a descriptive approach. The results of the study show that the concept of integrating religious knowledge and general science at Nurul Huda is inseparable from the basic values (qiyam HAM) that are embedded in every step and educational activity carried out in it. Nurul Huda Yaspin cults himself as a boarding school of etiquette, etiquette is an acronym for Takwa, Tafaqquh, Khidmah and rahmatan lil alamin. Nurul Huda's three basic values serve to underlie, integrate and direct his orientation. The application of the curriculum at Nurul Huda does not distinguish between religious knowledge and general science. In terms of concepts, religious knowledge and general science are both taught in recitations at Nurul Huda, such as Sufism, logic or mantiq lectures, philosophy, interpretation studies, falaq science and so on, all organized in curriculum units according to each study program. which is in Nurul Huda.